The impact of peer achievement and peer heterogeneity on own achievement growth: Evidence from school transitions - David Kiss (Friedrich-Alexander-Universität Erlangen-Nürnberg, Bavarian Graduate Program in Economics (BGPE), 2013)
This paper estimates ability peer effects on achievement growth in reading and math. It exploits variation in peer characteristics generated at the transition from primary to secondary school in a sample of Berlin fifth-graders. As will be discussed in detail, this variation is exogenous in large parts. Results are similar for both achievement measures: pupils benefit from abler peers, but high-achievers do so to a smaller extent. The estimated impact of the variance in peer skills is negative, but insignificant.
Keywords: I21; I28; 330; ability peer effects in upper-secondary school; natural experiment